If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2z + -10) = 12 Reorder the terms: 2(-10 + 2z) = 12 (-10 * 2 + 2z * 2) = 12 (-20 + 4z) = 12 Solving -20 + 4z = 12 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 4z = 12 + 20 Combine like terms: -20 + 20 = 0 0 + 4z = 12 + 20 4z = 12 + 20 Combine like terms: 12 + 20 = 32 4z = 32 Divide each side by '4'. z = 8 Simplifying z = 8
| -(-3x-9)+7=6x-1 | | (3x-5)+(2x)+(x)=139 | | 5n=440 | | 3(1.9-x)=4.5 | | 3(5c)+8=21 | | (-5u^2+7u-3)-(4u^2-2u+3)+(2u^2+2u-3)= | | 2x+(3x+5)=6 | | -3(3y+2)+9=-6 | | 180-x+11=3x+1 | | 5.1(6x+.07)-4.2=-1.5x+8.2 | | 3x^4+4x^3-36x^2+84=0 | | 3[60-s]-2s=105 | | 49=42x+4x^2 | | -9y+-6+9=-6 | | 6x-3(4x+5)=16 | | 12x+48=10x-4 | | 3x=7(4.322580645)-2 | | 3x-4+x+3x-4=55 | | 70=2x-10 | | 24m+42n-30= | | 3(10.5+-0.25y)=7y-2 | | 3x-4+x+3x-4= | | 10-6x+3x+2=57 | | 3=4+5y | | 9(10.5+-0.25y)=4x+1 | | 4(u+2)-7u=-10 | | 2x-3x-1=-5 | | 61-c=9 | | 3x^2-x^2+1600=0 | | 10(w+3)-14=66 | | 26=3(10.5+-0.25y)-2y | | -2(j-3)=-2j-6 |